Transgender Health Medical Education Intervention and its Effects on Beliefs, Attitudes, Comfort, and Knowledge - Cherabie, Joseph; Nilsen, Kari; Houssayni, Sarah (Kansas Journal of Medicine, 2018)
Introduction. Transgender health disparities have been well documentedin the literature in recent years, as have the lack of transgenderhealth issues in medical education programs across the country.Methods. A prospective study was conducted with an hour-longdidactic lecture on transgender health being given to faculty, medicalstudents, and residents at the University of Kansas School of Medicine-Wichita. The didactic lecture included educational informationand presentations by transgender persons. A pre-intervention andtwo post-intervention survey was given to assess attitudes, comfortlevel, knowledge, and beliefs regarding the treatment of transgenderedpersons and associated health concerns. A second post-interventionsurvey was given at 90 days. The question of what attendees plannedto do differently as a result of the intervention was asked.Results. The intervention provided a significant positive increase inattitudes, comfort levels, and knowledge with respect to transgenderhealth issues between the pre- and post-intervention surveys,however, did not provide a significant positive increase in beliefs ontransgender health issues. There was no significant change in attitude,comfort levels, knowledge, or beliefs from the post-survey after 90days. Four categories of what attendees planned to do differently as aresult of the intervention also were identified.Conclusions. A didactic lecture on transgender health issues canpositively change attitudes, comfort levels, and knowledge on transgenderhealth issues significantly with the changes sustaining after 90days. Beliefs tend to be much harder to change.Kans J Med 2018;11(4):106-109.